Interfaith Marriage Between Sunni And Shia: A Phenomenological Study In The Bondowoso Arab Community - Musdhalifah (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
This study aims to analyze phenomenologically related to the phenomenon of marriage across streams, between Sunnis and Shi'a, who have been known to have striking differences in beliefs. The difference is not only related to furu'iyah matters, but also related to things that are akidah. But in the Arab Community in Bondowoso has a unique phenomenon that makes Sunnis and Shi'a coexist, even holding marriages between them in order to become a strong familial relationship. This research uses a qualitative-based field research approach. The method used for the analysis of researchers used the phenomenological method of transendental Edmund Hurssel. This method researchers use to explain the meaning